Is Coronavirus a Concern on Fresh Produce? (Mandarin Chinese) - Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman; Michelle Danyluk (EDIS, 2020)
This is the Mandarin Chinese translation of FSHN20-22/FS350: Is Coronavirus a Concern on Fresh Produce?.  It provides guidance relevant to COVID-19 regarding handling and consumption of fresh produce. Written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman, and published by the UF/IFAS Food Science and Human Nutrition Department, May 2020.